Law Enforcement on Fiducian Security Objects Due to Withdrawal of Fiducia Security Objects - Angga Kusumah; Aryani Witasari (Universitas Islam Sultan Agung, 2021)
The objectives of this study are: Knowing and analyzing Law Enforcement against Fiduciary Guarantee Objects Post-Constitutional Court Decision Number 18 / PUU-XVII / 2019. Knowing and analyzing the obstacles that occur in law enforcement on the object of fiduciary security. In this research, the approach method used is the sociological juridical approach. The research specification used in this research is descriptive analysis. Based on the research, it is concluded that law enforcement on the object of fiduciary guarantee after the Constitutional Court Decision Number 18 / PUU-XVII / 2019 is preventive that has been carried out including: reading of rights and obligations and signing signatures by each party, registration of Fiduciary Security at the Ministry of Law and Human Rights, insuring units and parties, and give warning 3 (three) times before securing Fiduciary Security goods. The repressions that have been carried out include administrative law enforcement, criminal law enforcement and civil law enforcement. Constraints that Occur in Law Enforcement of the Object of the Fiduciary Guarantee and the solution is insufficient evidence, the solution is to look for such evidence; If the collateral object has not been found, the investigator needs to carry out further investigation; The suspect is not present, runs away, does not have a permanent place of residence or his identity is not clear, the solution is to carry out further investigations. Responding to the facts above, it is necessary that the Fiduciary Security Law be more socialized to the public,